Corrosão localizada do aço duplex UNS S32750 nitretado por plasma em baixas temperaturas - Palma Calabokis, Oriana (2020)
The UNS S32750 stainless steel is generally used in the oil and gas, chemical and petrochemical industries because of their high generalized and localized corrosion resistance. In the assembly of the machinery, there may be elements such as washers, screw heads, pipe supports and clamps, deposits on the surface, and in other surface heterogeneities, such as weld spatter and microorganism biofilms. Those elements generate occluded regions that can favor crevice corrosion and therefore, it could cause the catastrophic failure of machinery parts. One way to improve the localized corrosion resistance is the introduction of nitrogen into the steel. In this work, were accomplished low temperature plasma nitriding treatments (300°C, 350°C and 400°C, named as N300, N350 and N400). These treatments were performed in a pulse plasma reactor with a cold-wall chamber for 4 hours. A gas mixture composed of 70% N2, 20% H2 and 10% Ar were used in the nitriding process. The nitriding treatment formed a nitrided layer composed of expanded austenite (γN) without chromium or iron nitrides. The thickness of this layer was increased from 0,94 ± 0,10 µm to 2,99 ± 0,32 µm, as the treatment temperature increases. The maximum hardness value was HV0.025 = 879 ± 136 for N400, compared to the hardness value of untreated condition HV0.025 = 338 ± 13. All the nitrided conditions exhibited lower corrosion rates, the formation of a more protective passivation layer and a better repassivation capacity, compared to untreated condition. Those results were obtained by cyclic polarizations test in 3.5% NaCl solution. Finally, the susceptibility to crevice corrosion was assessed by an adaptation of the standard ASTM G192-08. The nitrided conditions (N350 and N400) presented lower susceptibility to crevice corrosion. Those conditions had lower current density during the potentiostatic stage in both the passive (1.2 V) and in the transpassive (1.5 V) potentials. Also, they showed smaller corrosion depths compared to untreated condition. Duplex UNS S32750 and its nitrided conditions (N350 and N400) were completely resistant to crevice corrosion when they were polarized at the passive potential (1.2 V). The results confirm the beneficial effect of low temperature plasma nitriding on the crevice corrosion and general corrosion resistances of the UNS S32750 duplex steel.